2003
DOI: 10.1115/1.1543972
|View full text |Cite
|
Sign up to set email alerts
|

On the Improvement of Calibration Coefficients for Hole-Drilling Integral Method: Part II—Experimental Validation of Calibration Coefficients

Abstract: Experimental validation of the calibration coefficients for integral hole-drilling method obtained from an improved three-dimensional FEM model was achieved using bending test of a cantilever beam. The experimental setup is a simple yet accurate method to validate the calibration coefficients obtained by a three-dimensional FEM model. With this experiment, we also validate the adequacy of the criterion applied for thin or thick plates in a previous work. The relieved stresses calculated from the calibration co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
0
5
0
3
Order By: Relevance
“…An assumption of an infinitely large sample was made in order to calibrate the coefficients by either experiments [3] or FEM [1, 2, 6–8]. Some studies were conducted on the calibration coefficients’ sensitivity to the thickness of the model, while assuming the model is an infinite plate, and it was found out that the thickness affects the coefficients significantly—especially when the thickness is less than 1.5 times of mean radius of rosette ( r m ) [6, 7]. In reality, the measurements are often made on a narrow surface, where the coefficients must be calibrated according to its real dimension.…”
Section: Factors Influencing the Calibration Coefficientsmentioning
confidence: 99%
See 1 more Smart Citation
“…An assumption of an infinitely large sample was made in order to calibrate the coefficients by either experiments [3] or FEM [1, 2, 6–8]. Some studies were conducted on the calibration coefficients’ sensitivity to the thickness of the model, while assuming the model is an infinite plate, and it was found out that the thickness affects the coefficients significantly—especially when the thickness is less than 1.5 times of mean radius of rosette ( r m ) [6, 7]. In reality, the measurements are often made on a narrow surface, where the coefficients must be calibrated according to its real dimension.…”
Section: Factors Influencing the Calibration Coefficientsmentioning
confidence: 99%
“…No exact solution for a blind hole into a field of plane stress is yet available from the theory of elasticity, although there was a closed form of the residual stresses calculation from strain relieved for cutting a through‐hole on a thin plate [3–5]. The calibration coefficients for blind‐hole method can be determined experimentally [3] or via numerical simulation with FE model [1, 2, 6, 7]. Some dimensionless calibration coefficient tables were obtained by using a 2‐Dimensional Finite Element (2‐D FEA) model, and it was reported that the calibration coefficients for any specific testing case can be interpolated from the dimensionless calibration coefficient data tables [1, 2].…”
Section: Introductionmentioning
confidence: 99%
“…The most recent standard ASTM E837‐08 [7] takes into account also the non‐uniform residual stresses problem, suggesting the use of the integral method to calculate the residual stress distribution by means of the influence coefficients available for some strain gauge rosette geometries. It is well known that the IHD can be affected by several kinds of experimental errors and uncertainties [8–12]. After a round robin test programme, Grant et al.…”
Section: Introductionmentioning
confidence: 99%
“…Although the two stress distributions have different trends, the proposed test rig allows to measure the bending stress relaxed strain and the residual stress relaxed strain on the same specimen at each hole depth increment, to have complete confidence of no alteration of the experimental set‐up between the residual stress measurement and the measurement verification. Previously, other investigators proposed the verification of the IHD using a reference bending [11, 12] too, but these verifications of the IHD were not performed together with any residual stress measurements. These investigators experimentally demonstrated that the IHD method works, but this does not prevent any unexpected hardware malfunctioning due to the operator inexperience, or any error during the inverse problem calculation, when performing a single residual stress measurement.…”
Section: Introductionmentioning
confidence: 99%
“…Definieron los espesores adecuados para placas delgadas y gruesas y propusieron los coeficientes de calibración para ciertos casos que después validaron experimentalmente [Aoh03].…”
Section: Espesor De Las Probetasunclassified